Juvenile court outcomes following youth’s first arrest: a national test of the racial and ethnic threat hypothesis - Andersen, Tia S. (Crime & delinquency, 2019)
Using nationally representative data, this research examined the associations between indicators of minority threat and juvenile justice processing following a first arrest. At intake, increasing Black presence in the community resulted in leniency, rather than severity. Once adjudicated, the size of the Black population had a nonlinear inverted-U shaped relationship with probability of placement. Increasing Hispanic presence was associated with leniency in disposition, and economic threat was not significantly related outcomes. Indicators of minority threat did not exacerbate outcomes for minority youth. These findings suggest that, contrary to the expectations of minority threat theory, the growing presence of minorities in communities may weaken social control and harsh punishments, particularly once the size of the minority population reaches a critical threshold.